PENGARUH TINGKAT SUKU BUNGA TABUNGAN, PRODUK TABUNGAN DAN KUALITAS PELAYANAN TERHADAP MINAT MENABUNG NASABAH PADA BPR INDRA CANDRA SINGARAJA - Komang Trisna Sari Dewi; Luh Putu Putri Sariani (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2022)
The purpose of this study was to determine the effect of saving interest rates, savings products and service quality on customer interest in saving at BPR Indra Candra Singaraja. The population in this study are customers who save at BPR Indra Candra Singaraja while the sample in this study is 75 customers. Methods of collecting data by using questionnaire techniques and data analysis techniques using the application SPSS Versi 18.0. The results showed that the t-test value of the effect of interest rates on savings savings customers obtained a t-count > t-table (2.962 > 1.666) with a probability value (a = 5%) = 0.004 < 0.05, the effect of the product savings on customer interest in saving, the value of t-count > t-table (5.392 > 1.666) with probability value (a = 5%) = 0.000 <0.05 and the effect of service quality on customer interest in saving is obtained by t-count > t- table (3.980 > 1.666) with probability value (a = 5%) = 0.000 < 0.05. The results of this study indicate a positive and significant influence between interest rates on savings, savings products, service quality on customer interest in saving at BPR Indra Candra Singaraja.